Development of ARDS after Excessive Kath Consumption: A Case Report. (24th July 2011) - Wewalka, Marlene; Drolz, Andreas; Staufer, Katharina; Scherzer, Thomas M.; Fuhrmann, Valentin; Zauner, Christian
Abstract : Khat is a drug widely used in the Horn of Africa and the Arabian Peninsula. Khat leaves contain, among other substances, the psychoactive alkaloid cathinone, which induce central nervous system stimulation leading to euphoria, hyperactivity, restlessness, and insomnia. However, it also could cause psychological adverse effects such as lethargy, sleepiness, psychoses, and depression necessitating pharmacologic treatment. Here we report the case of a 35-year-old man from Somalia who became unconscious and developed aspiration pneumonia and subsequent ARDS after excessive consumption of khat leaves. His unconsciousness was possibly caused by the sleepiness developed after khat consumption and a benzodiazepine intake by the patient himself. Thus, khat-induced adverse effects should not primarily be treated pharmacologically, but patients should be urged to quit khat consumption in order to eliminate or, at least, reduce the severity of present psychological adverse effects.